The Application and Development of Mobile Internet in Educational Informatization in Liangshan - Song, Xiaorong (Journal of Theory and Practice in Education and Innovation, 2024)
Education informatization is an important link to realize the modernization of national education. Integrating mobile Internet technology with education is an important means to realize national education informatization. Since China is a multi-ethnic country, it is indispensable to study education in ethnic minority areas in order to fully realize education modernization. Through the analysis of the relevant literature on education informatization in ethnic areas, we can understand the problems in the education informatization of ethnic areas. Taking the education informatization of Liangshan Prefecture as a typical example, it focuses on the application and development of mobile Internet in Liangshan Prefecture education informatization. Try to accelerate the process of education informatization in ethnic areas from the aspects of infrastructure construction, education resource cloud platform construction, distance education, teacher training, and investment channels.